Front Cover: Quantum Computers as Universal Quantum Simulators: State‐of‐the‐Art and Perspectives (Adv. Quantum Technol. 3/2020). Issue 3 (6th March 2020) - Tacchino, Francesco; Chiesa, Alessandro; Carretta, Stefano; Gerace, Dario
Abstract : Qubit‐based quantum processors can be programmed to compute the dynamics of a large class of complex many‐body models. The cover gives a pictorial view of the key ingredients allowing to perform quantum computer simulations: a mathematical description of the dynamics of a physical system and its mapping on a spin lattice representation, which can ultimately be encoded onto a given quantum hardware backend. In article number 1900052, Dario Gerace and co‐workers review the relevant theoretical background and the main technological platforms currently realizing this paradigm.